Kemampuan Komunikasi Matematis Siswa Madrasah Aliyah melalui Model Pembelajaran Kooperatif Tipe Jigsaw - Rahmat Rahmat; M. Ikhsan; Cut Morina Zubainur (Jurnal Peluang, 2019)
The ability of mathematical communication is one of the goals of learning in mathematics. communications skills can be defined as the ability in writing, reading, listening, analyzing, interpreting, and evaluating ideas, symbols, terms, and information mathematics. Therefore, it is necessary that relevant learning model to optimize, improve and develop the students' mathematical communication skills. One model of learning is cooperative learning model Jigsaw. The purpose of this study to determine: (1) Is the improvement of communication capabilities mathematical students taught by cooperative learning model Jigsaw better than that taught conventionally, and (2) the interaction cooperative learning model Jigsaw with prior knowledge of students' mathematical communication students. This research is experimental research design pretest-posttest Control Group Design. The population in this study were all students of class XI MAN Peusangan Bireuen district consists of four classes. While the sample is composed of two classes, namely the experimental class and control class taken by random sampling. The instrument used to obtain research data in the form of mathematical communication ability test. The statistical test used to upgrade data mengalisis mathematical communication skills are a test of Anova two lanes. The results showed that the overall improvement of communication capabilities mathematical students taught by cooperative learning model Jigsaw better than students taught by conventional approach. There is no interaction between cooperative learning model Jigsaw with initial ability of students to the students' mathematical communication skills.